Kekuatan Kolaboratif antara Kelompok Guru dan Pemerintah dalam Implementasi Program Makan Bergizi Gratis di Sekolah Dasar - Lilis Nurhalimah; Evi Putri Meilina; Muhammad Lintang Fajar; Didik Tri Setiyoko (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The Free Nutritious Meal Program (MBG) is a national priority policy under the Prabowo–Gibran administration aimed at improving students’ well-being and learning quality through school-based nutrition interventions. However, its effectiveness largely depends on the collaborative strength between teacher groups as field implementers and the government as policy makers. This study aims to analyze the collaborative synergy between teachers and the government in implementing MBG and to develop a conceptual model of school-based partnership. The study employs a Systematic Literature Review (SLR) method, reviewing national and international articles published between 2018 and 2024 using keywords “free nutritious meals”, “school feeding program”, “government collaboration”, and “primary school teachers”. Thematic analysis was conducted by categorizing findings into four main themes: the role of government, the role of teachers, collaborative implementation, and impact on students. The results show that the success of MBG depends on policy transparency, teacher training, and cross-sector coordination responsive to local conditions. This article contributes to constructing a conceptual collaborative model that positions teachers as policy mediators and social change agents in schools. The findings strengthen the concepts of collaborative governance and empowerment education within the context of educational nutrition policy in Indonesia.